Consumers and firms in international trade - Christian Volpe Martincus; Monika Sztajerowska; Mariana Santi (Inter-American Development Bank (IDB), 2024)
Modern theoretical and empirical analyses in international trade typically focus on firms as the sole trading actors. This is consistent with the fact that firms have traditionally accounted for the vast majority of trade and, hence, examining their behavior allows for fully characterizing trade margins and assessing their determinants. Emerging and rapidly growing trade modalities such as cross-border e-commerce have started to change this by making it easier for individuals to directly engage in international sales and purchases. However, to what extent and how consumers directly participate in and shape international trade has remained largely unknown due to data limitations. In this paper, we use a unique dataset consisting of the entire universe of import shipments that entered Peru in 2019 to provide novel evidence on the role of both consumers and firms as importers, characterize the distribution and patterns of their foreign purchases, and assess how gravity forces shape their trade decisions, thus filling in this gap in the literature.
Keywords: F13; F14; 330; International Trade; Consumers; Firms; Gravity